THE EFFECT OF NONI LEAF (Morinda citrifolia L.) EXTRACT WATER BY DRINKING WATER TO EGG PRODUCTION OF LOHMANN BROWN LAYING HENS AGE OF 22-30 WEEKS - H. H., Widoretno; Utami, I. A. P.; Bidura, I G. N. G. (Jurnal Peternakan Tropika; Vol 6 No 2 (2018): May - August 2018, 2018)
This study aim was to find out the effect of noni leaf (Morinda citrifolia L.) extract water given into drinking water to egg production of Lohmann Brown the age of 22-30 weeks. Research in Dajan Peken village, Tabanan sub-district-Bali for 3 months with 36 Lohmann Brown chicken the age of 22 week as material. The design used is complete randomized design with 3 treatments and 6 replications. Such treatment: without added noni leaf (Morinda citrifolia L.) water extract  as control (A); B: with 2% noni leaf (Morinda citrifolia L.) water extract; and C; with 4% noni leaf (Morinda citrifolia L.) water extract. Variables obserbed were feed consumption, water consumption, feed converation ratio, total egg production, average egg weight and total egg weight. The results obtained were tested by multiple analysis from Duncan. The results showed that giving leaf water extract of noni leaf into drinking water at level 2% and 4% significantly able to increased feed consumption, water consumption, total egg production, average egg weight, total egg weight and reduced feed conversion ratio value on Lohmann Brown chicken the age of 22-30 weeks. The conclusion of this study is giving water extract of noni leaf at level 2% and 4% into drinking water can significantly increase egg production and reduced feed conversion ratio value of Lohmann Brown chicken aged 22-30 weeks. Keywords: noni  leaf,  egg production, Lohmann Brown chicken